Work-Environment Predictors of Burnout Among Psychiatric Nurses in Indonesia - Aquila Azizah; Indriati Paskarini; Mahmudah; M. Shalehuddin (Jurnal Kesehatan Masyarakat, 2026)
Healthcare professionals, particularly nurses, operate in demanding environments that require advanced expertise and considerable responsibility. Nurses frequently encounter heavy workloads, increasing their susceptibility to burnout. This risk is heightened among psychiatric nurses, who routinely care for patients with mental disorders and must address complex emotional challenges. In the present study, 22.22% of participating nurses reported experiencing burnout as a result of aggressive patient behavior. Methods: This cross-sectional study involved 180 nurses selected through stratified random sampling from outpatient, inpatient, emergency, and Intensive Psychiatric Care Unit (IPCU) settings at Dr. Radjiman Wediodiningrat Psychiatric Hospital. Environmental factors were assessed using the Copenhagen Psychosocial Questionnaire III, while burnout was measured with the Maslach Burnout Inventory. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the association between environmental factors and burnout. Results: A statistically significant negative association was identified between environmental factors and burnout among nurses (path coefficient = -0.355, p-value < 0.05). The most influential environmental indicators included community relationships, work values, and perceived fairness. Higher levels of these indicators corresponded with lower levels of burnout. Conclusion: Environmental factors, especially community relationships, work values, and fairness, play a critical role in reducing burnout among psychiatric hospital nurses. Interventions focused on these factors may enhance nurse well-being and improve the quality of care.